Cultivation of Plants About Planting Distance of Kale Withdraw in Pattiro Riolo Village, Sibulue District, Bone Regency - A. Besse Dahliana; Andi Rismayanti Fianda Sari; Hujemiati; Jumardi (PT FORMOSA CENDEKIA GLOBAL, 2023)
KKLP students from the Yapi Bone College of Agricultural Sciences carried out a work program on Plant Cultivation About Distance to Plant Kale Withdrawn in Pattiro Riolo Village, Sibulue District, Bone Regency by utilizing empty land owned by local residents as an experimental land. Kale plants are classified as a type of vegetable that is very popular in society. The materials used in this experiment of kale plants were the seeds of the Bangkok LP-1 land kale variety, and used cow manure, Bioboost biological fertilizer, water, organic pesticides. The number of treatment combinations obtained was 4 x 4 = 16 combinations, namely: S0H0, S0H1, S0H2, S0H3, S1H0, S1H1, S1H2, S1H3, S2H0, S2H1, S2H2, S2H3, S3H0, S3H1, S3H2, S3H3. With 3 repetitions, 48 plots were obtained, the distance between plots was 40 cm and the distance between replicates was 60 cm, the plot size was 100 cm x 100 cm, so 25 plants/plot were obtained and the plant spacing was 20 cm x 20 cm and a total of 1200 plants. Land spinach seedlings are planted in prepared beds. Planting holes are made with a spacing of 20 cm x 20 cm, and in each hole one seed of kale is planted. Watering is done in the morning and evening depending on the weather conditions. When the weather is raining, watering does not need to be done with a note that the rainwater is sufficient for the needs of the kale, and insertion is done on 4 - 7 HSPT (Day after Transplanting) and to prevent the kale plants from pests and diseases, control is carried out every week . Initially, control was carried out manually by killing visible pests on the plants and removing dead or severely attacked plants. After that, the kale can be harvested at the age of 25 HSPT